The green mile : the complete serial novel - King, Stephen, 1947-; Geyer, Mark. (New York : Pocket, 1999)
Welcome to Cold Mountain Penitentiary, home to the Depression-worn men of E Block. Convicted killers all, each awaits his turn to walk the Green Mile, keeping a date with "Old Sparky," Cold Mountain's electric chair. Prison guard Paul Edgecombe has seen his share of oddities in his years working the Mile. But he's never seen anyone like John Coffey, a man with the body of a giant and the mind of a child, condemned for a crime terrifying in its violence and shocking in its depravity. In this place of ultimate retribution, Edgecombe is about to discover the terrible, wondrous truth about Coffey, a truth that will challenge his most cherished beliefs.
Part One: The Two dead girls. -- Part Two: The Mouse on the mile. -- Part Three: Coffey's hands. -- Part Four: The Bad death of Eduard Delacroix. -- Part Five: Night journey. -- Part Six: Coffey on the mile.
"Illustrations, Mark Geyer."--T.p. verso.
910
Keywords: Death row inmates -- United States -- Fiction; Serialized fiction; Horror fiction